Association between gut microbiota and acute upper respiratory tract infection: a Mendelian randomization study - Yuexing Li; Guanglei Chen; Ke Chen; Wen Li; Yunzhi Chen (Scientific Reports)
Abstract Targeting specific gut microbiota (GM) species to prevent and treat acute upper respiratory tract infection (AURTI) has attracted researchers’ attention, but the relationship between the two is unclear. Based on the summary data from genome-wide association studies (GWAS) on GM and five types of AURTIs (acute nasopharyngitis (common cold), acute pharyngitis, acute sinusitis, acute upper respiratory infections, and acute upper respiratory infections of multiple and unspecified sites), we performed two-sample bidirectional Mendelian randomization (MR) to assess the causal relationship. Through inverse variance weighting (IVW) method, we found that 33 potential microbial taxa can influence the occurrence of AURTI. Sensitivity analysis showed no potential horizontal pleiotropy and heterogeneity bias. We further employed multivariable Mendelian randomization to investigate the impact of potential interference factors on the significant associations previously identified, considering aspects such as comorbidities associated with AURTI, seasonal variations, pathogen specificity, and history of antibiotic allergies. Ultimately, 11 microbial taxa remained significantly associated. This study provides robust evidence for a causal relationship between GM and five types of AURTIs, thereby offering a foundation for the development of microbiota-targeted therapies and related probiotic interventions aimed at AURTI.